Isolasi dan Karakteristik Bakteri Pada Air Gambut di Kawasan Desa Sungai Daun Kecamatan Pasir Limau Kapas Kabupaten Rokan Hilir Provinsi Riau - Ismiati Ismiati; Ida Fauziah; Rahmiati Rahmiati (Universitas Medan Area, 2020)
Water color intensity is associated with topsoil concentration. The lower color intensity the lower topsoil concentration, pH and temperature. Peat water characteristic were determined by accumulation of Natural Organic Matter. The study was conducted on November 2017 to February 2018 in Health Laboratory of North Sumatera by using 3 samples of peat water to find out characteristics of peat water bacteria. Isolated bacteria were analysed by macroscopic and microscopic examination. The result showed that the bacteria have various morphology and motility. Based on characteristics, sp1 was suspected to be in the group of Staphylococcus genus while sp2 and sp3 were belong to the Escherichia genus.